Can the African weaver ant be used as a vector of entomopathogenic fungi to bolster the biological control of tephritid fruit fly pests? - Thibault Nève de Mévergnies; Samba Diop; Massamba Diakhaté; Claire Detrain; Frédéric Bouvery; Thierry Brévault; Anaïs Chailleux (Biological Control)
Entomovectoring is an environmentally friendly pest control strategy where insects act as precision vectors of a biocide to target pest populations through phoretic dispersal. While bumblebees are the only insects used commercially for this purpose, other insect species, including ants, offer untapped potential. The arboreal weaver ant, Oecophylla longinoda, known for its beneficial predatory role in production crops, could be used as a vector of the entomopathogenic fungus, Metarhizium anisopliae to bolster control of the invasive oriental fruit fly Bactrocera dorsalis. In this study, we set up a series of experiments under laboratory and mesocosm conditions to investigate the feasibility of using this ant as an entomovector. Results showed that while M. anisopliae was intrinsically pathogenic to the weaver ants, they were able to detect its presence and adjust their behavior according to its concentration. Despite exposure, the ants effectively protected themselves through social immunity behaviors. Furthermore, weaver ants auto-inoculated themselves with conidia by walking over contaminated areas and subsequently dispersed conidia along their trails. Although the density of dispersed conidia declined over time and distance from the inoculation zone, up to 36% of fruit flies were killed when left to roam on mango trees where conidia had been disseminated by the weaver ants. While the integration of weaver ants as pathogen entomovectors could enhance pest fruit fly control when combined with other strategies, several challenges are yet to overcome before field applications.